A piedade popular em tempos líquidos na Sacrosanctum Concilium 13 - Cardoso, João Paulo (2018)
According to Sacrosanctum Concilium 13, pious exercises should be recommended, but with determination that there should be harmonization with the liturgy. The Popular Piety can not substitut, in any way, the official liturgical practices of the Church. In this study we make analysis of the current reality, which will be based on ‗Liquid Modernity‘, expression of the Polish Sociologist Zygmunt Bauman. With this expression, Bauman identify the moment we are living, in which everything is predicted to be fleeting, including the human relations. In this context, the harmonization between Liturgy and Popular Piety is impaired, causing a mismatch between liturgical practices, with their stable norms, and popular devotions, prone to change more easily. However, pious exercises should be encouraged, even with the variants of the present time. For this analysis, the theoretical foundations are sought in the Directory on Popular Piety and the Liturgy, documents of the Popes, in the set of works written by Bauman and many others that help in understanding of the relation between the Popular Piety and the Liturgy in this period of history which Bauman classifies as ‗Liquid Modernity